2008
DOI: 10.1007/s11606-008-0855-y
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Physician-patient Discussion of Breast Reconstruction

Abstract: BACKGROUND: For women with early stage breast cancer, physician-patient discussion of breast reconstruction is an essential step in their participation in the decision-making process for their treatments. This study examines sociodemographic variation of physician-patient discussion of breast reconstruction and explores the impact of this discussion on the use of breast reconstruction. METHODS:We used data from the Los Angeles Women's Study, a population-based study of women 50 years and older with breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 36 publications
2
27
1
2
Order By: Relevance
“…More recently, another population-based study of survivors in Los Angeles found that 19% reported no discussion of reconstruction with their provider. 6 Lower-income women in that study were less likely to have discussed reconstruction with their provider.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…More recently, another population-based study of survivors in Los Angeles found that 19% reported no discussion of reconstruction with their provider. 6 Lower-income women in that study were less likely to have discussed reconstruction with their provider.…”
Section: Discussionmentioning
confidence: 76%
“…Up to twenty percent of breast cancer survivors have reported they were never told about reconstruction, 6, 7 and ethnic minority women appear to be least informed about reconstruction. 8 Patients who have had reconstruction have expressed regret about having it and the feeling that their goals were not met.…”
Section: Introductionmentioning
confidence: 99%
“…In retrospective studies, approximately 20% of women who had mastectomy reported no discussion about breast reconstruction with their provider. 1, 6, 8 Minority women are less likely to report a discussion about breast reconstruction, 1, 4, 6 and they have lower knowledge about reconstruction. 8 Concern also exists because many women are unsatisfied with their choice to receive or not receive reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Patient decision-making should be focused on her values [27]. Comprehension and knowledge retention of breast reconstruction facts may be low [26].…”
Section: Patient Values and Preferences: Weights And U-valuesmentioning
confidence: 99%